Optimization algorithms for ultrasonic array imaging in homogeneous anisotropic steel components with unknown properties. (December 2020) - Ménard, Corentin; Robert, Sébastien; Miorelli, Roberto; Lesselier, Dominique
Abstract: In this paper, we investigate the ability of an adaptive ultrasonic method to image point-like reflectors inside anisotropic and homogeneous nuclear steels with unknown properties, such as V-shape welds or cladded components. The optimization scheme combines the Total Focusing Method (TFM) imaging algorithm with a customized gradient ascent method to improve both the quality and the reliability of ultrasound images. A statistical analysis of its robustness is performed with simulated echoes and using a surrogate model to speed up the computation times of the TFM images. Then, the optimization procedure is evaluated with several experimental cases and provides highly enhanced images with a 5 MHz array. The positioning of the artificial defects of 2.0 mm diameter is estimated with less than 1 mm error with respect to their actual position, and the signal-to-noise ratio is increased by up to 10 dB. The elastic properties are also estimated with less than 10% error when compared to their actual values. Highlights: This work aims to enhance ultrasonic images in unknown anisotropic steels. An optimization procedure iteratively modifies the unknown parameters of the theoretical model describing the material to optimize the quality of TFM images. A numerical study demonstrates the robustness of the optimization procedure. Experiments performed with an Inconel V-shape weld and a cladded steel component validate the efficiency of the optimization to produce high quality TFM images. Considering homogeneous structures, the procedure is also able to yield faire estimates of the material parameters.